The The Effect strategic administration of the activists and the advanced organization has achievement in the subject of history - Ahmed, Sherzad; Aziz, Karim; Abdullah, Salam (Humanities Journal of University of Zakho, 2023)
The aim of this study is to investigate the effect of stimulants of cognitive strategy and advance organizers on the students’ learning achievement from the Department of Social Sciences at the subject of the medieval history of the Kurds . The study sample consisted of second year students at the Department of Social Sciences Selecting such a sample of students is due to two reasons: the suitability of this stage and teaching the history of the Kurds in the Middle Ages in this stage. The researcher used a quasi-experimental research design, where the research included three balanced groups (two experimental groups and one control group), the first experimental group received the material according to the strategy of cognitive stimulants, the second experimental group received the material according to the strategy of the advance organizers, and the third group( control group) received the material according to the usual method, and each group consisted of 19 students (males and females) . The researcher designed an achievement test based on the study. The study included 40 multiple-choice items. After administering the test and collecting data, the researcher used SPSS software to analyze the data . The results arrived at in this study showed that stimulants of cognitive strategy was a successful method for teaching history. The first experimental group achieved better learning, and the strategy of advance organizers was successful and effective for history subjects among students of the Department of Social Sciences.